Consumer Preferences for Imported Longan Fruit in Pangkalpinang City - Rahmawati; Muntoro Muntoro; Eddy Jajang Jaya Atmaja (Journal of Global Sustainable Agriculture, 2025)
This study aims to analyze consumer preferences for longan fruit and analyze longan attributes, which are most considered in purchasing decisions. Data collection was carried out from March to April 2024 in Pangkalpinang City. The research method used in this study was a survey. While the sampling method in this study was the accidental sampling method with the number of respondents studied as many as 100 respondents. The research data was analyzed using conjoint analysis. The results of the study showed that consumer preferences in Pangkalpinang City for longan fruit attributes were longan fruit with a sweet taste, thick fruit flesh, large fruit size, non-watery fruit, and imported longan fruit with values ​​of utility respectively (1.145), (0.305), (0.292), ((0.170) and (0.089). The order of longan fruit attributes based on the level of importance according to consumer preferences is taste, thickness of fruit flesh, size, water content, and type of longan fruit with values ​​respectively (58.17), (14.09), (13.19), (9.14) and (5.41).